Convergence rates in a weighted Fucik problem - Salort, Ariel Martin (2013)
In this work we consider the Fučik problem for a family of weights depending on ε with Dirichlet and Neumann boundary conditions. We study the homogenization of the spectrum. We also deal with the special case of periodic homogenization and we obtain the rate of convergence of the first non-trivial curve of the spectrum.